Pengaruh Rekrutmen dan Pelatihan Kerja terhadap Kinerja Karyawan di PT Inasentra Unisatya - Retno Nurcholis; Ulta Rastryana (STIKes Ibnu Sina Ajibarang, 2024)
The main aspect that needs to be considered by organizations or companies to achieve their goals is the HR aspect. Therefore, companies need to pay more attention to employee performance to be even better, especially in terms of recruitment and job training. This study aims to determine the effect of recruitment and job training on employee performance at PT. Inasentra Unisatya. The research method used is a quantitative approach. Data collection methods in this study are interviews, observations, questionnaires, and literature studies. The population in this study were permanent employees of PT. Inasentra Unisatya in the field of personnel as many as 53 employees. The sampling technique used was a saturated sample with a sample size of 53 respondents. The data analysis techniques used were data quality testing, classical assumption testing, hypothesis testing, and determination coefficient testing processed using the SPSS version 25.0 application. The results of this study indicate that partially recruitment has a positive and significant effect on employee performance. Partial job training has a positive and significant effect on Employee Performance. Simultaneously recruitment and job training have a positive and significant effect on employee performance.